ANALISIS KINERJA PEMERINTAH DALAM PENANGANAN PENGUNGSI ERUPSI GUNUNG SINABUNG SERTA DAMPAK TERHADAP SOSIAL EKONOMI MASYARAKAT KABUPATEN KARO. - Sumbul Sembiring Depari; Ingan Ukur Br Sitepu (JURNAL REGIONOMIC, 2018)
Karo regency is a one of 33 Regency of North Sumatera Province wich geographically lies at Bukit Barisan Highland Mountain and 75 km from Medan, the capital of North Sumatera Province. Karo regency have two mount, mount Sinabung and mount Sibayak, and one of them, mount Sinabung in the year of 2010 have erupted and again 2013 erupted until now. These eruption created 6179 refugees that located in many location as refugees. Economically, according to local government of Karo Regency, the economic growth decreased from 6,34% 2012 to 4,71% in 2013. Then, since 2014 economic growth increase to 5.09% and 2015 become 5,01% perannum. The total Loss of society and government property around Rp 964,035 miliard which consist of agriculture field Rp 712,185 miliard, housing Rp 234,75 miliard and others Rp 17,1 miliard. In terms of tourism sector, the total of tourist visited karo regency decreased dramatically not only frainner but also local visitor. The total budget need for recovery post eruption Rp 506,653 miliard and, for rehabilitation and reconstruction Rp803,525 miliard (bappeda kab.karo). In terms of performance quality BPBD karo regency to serve all refugees based on survey, from 75 respondent of 287 population to the quistionaire result shown 0,534 by used statistical metod. It’s mean that there are positive and significant the relationship between the good performance of local government of karo regency toward sastisfied of refugees to received served as long there are at refugees location